Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the zeros of the quadratic equation [tex]\( y = x^2 + 4x - 9 \)[/tex] by completing the square, follow these steps:
1. Rewrite the equation:
[tex]\[ x^2 + 4x - 9 = 0 \][/tex]
Move the constant term to the other side of the equation:
[tex]\[ x^2 + 4x = 9 \][/tex]
2. Complete the square:
To complete the square, add and subtract the same value inside the equation. We take half of the coefficient of [tex]\( x \)[/tex], square it, and add it to both sides of the equation.
The coefficient of [tex]\( x \)[/tex] is 4. Half of 4 is 2, and [tex]\( 2^2 = 4 \)[/tex]. Thus, we add 4 to both sides:
[tex]\[ x^2 + 4x + 4 = 9 + 4 \][/tex]
[tex]\[ (x + 2)^2 = 13 \][/tex]
3. Solve for [tex]\( x \)[/tex] by taking the square root of both sides:
[tex]\[ x + 2 = \pm \sqrt{13} \][/tex]
[tex]\[ x = -2 \pm \sqrt{13} \][/tex]
So, the zeros of the equation [tex]\( y = x^2 + 4x - 9 \)[/tex] are:
[tex]\[ x = -2 + \sqrt{13} \quad \text{and} \quad x = -2 - \sqrt{13} \][/tex]
Therefore, the correct answer is:
[tex]\[ D. \, x = -2 \pm \sqrt{13} \][/tex]
1. Rewrite the equation:
[tex]\[ x^2 + 4x - 9 = 0 \][/tex]
Move the constant term to the other side of the equation:
[tex]\[ x^2 + 4x = 9 \][/tex]
2. Complete the square:
To complete the square, add and subtract the same value inside the equation. We take half of the coefficient of [tex]\( x \)[/tex], square it, and add it to both sides of the equation.
The coefficient of [tex]\( x \)[/tex] is 4. Half of 4 is 2, and [tex]\( 2^2 = 4 \)[/tex]. Thus, we add 4 to both sides:
[tex]\[ x^2 + 4x + 4 = 9 + 4 \][/tex]
[tex]\[ (x + 2)^2 = 13 \][/tex]
3. Solve for [tex]\( x \)[/tex] by taking the square root of both sides:
[tex]\[ x + 2 = \pm \sqrt{13} \][/tex]
[tex]\[ x = -2 \pm \sqrt{13} \][/tex]
So, the zeros of the equation [tex]\( y = x^2 + 4x - 9 \)[/tex] are:
[tex]\[ x = -2 + \sqrt{13} \quad \text{and} \quad x = -2 - \sqrt{13} \][/tex]
Therefore, the correct answer is:
[tex]\[ D. \, x = -2 \pm \sqrt{13} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.